The Rule of Law and the Principle of Equality Before the Law: Theory and Its Manifestation in Indonesia - Marzuki, Ismail (Jurnal Idea Hukum, 2024)
The rule of law and the principle of equality before the law require the lives of the nation and state without arbitrariness and discrimination. The state constitution should provide protection to citizens; in judicial practice, it turns out that not a few justice seekers, especially ordinary people, find injustice. The purpose of this research is to examine the concept of the rule of law and the principle of equality before the law philosophically, and what its manifestations are in Indonesia. This study uses a normative juridical method with a legislative approach and a conceptual approach. The results show that the rule of law talks about "everyone" not "this group and that group.” While the principle of equality before the law contains the principle that all men are created as equal, that everyone is created as equal, especially with regard to basic human rights. Thus, the principle of equality before the law in the concept of the rule of law in Indonesia is believed to bring justice (access to justice) to anyone regardless of background because the essence of human beings has the same degree and therefore there should be no discriminatory treatment for any reason. Therefore, the conclusion of this research states that in the Indonesian state of law, the principle of equality before the law is not only formulated in the state constitution but is also recognized in various laws and regulations under it. In addition, the principle of equality before the law was implemented in various fields of citizens' lives, including the judicial world in Indonesia.